Phaffia brasiliana sp. nov., a yeast species isolated from soil in a Cerrado–Atlantic Rain Forest ecotone site in Brazil. Issue 11 (2nd November 2021) - Santos, Ana Raquel Oliveira; Aires, Andreia; Pontes, Ana; Silva, Margarida; Brito, Patricia H; Groenewald, Marizeth; Melo, Cidiane G. S.; Lachance, Marc-André; Sampaio, José Paulo; Rosa, Carlos A.
Abstract : During studies of yeasts associated with soil in a Cerrado–Atlantic Rain Forest ecotone site in Brazil, three orange-pigmented yeast strains were isolated from samples collected in Minas Gerais state, Brazil. Molecular analyses combining the 26S rRNA gene (D1/D2 domains) and the internal transcribed spacer (ITS) sequences as well as whole-genome sequence data showed that these strains could not be ascribed to any known species in the basidiomycetous genus Phaffia, and thus they are considered to represent a novel species for which the name Phaffia brasiliana sp. nov. is proposed. The holotype is CBS 16121 T and the MycoBank number is MB 839315. The occurrence of P. brasiliana in a tropical region is unique for the genus, since all other species occur in temperate regions. Two factors appear to contribute to the distribution of the novel taxon: first, the region where it was found has relatively moderate temperature ranges and, second, an adaptation to grow or withstand temperatures higher than those of the other species in the genus seems to be in place.